AL-KHAIRAAT SEBAGAI LEMBAGA PERJUANGAN BANGSA - Nurinayah Nurinayah (Program Studi Hukum Tata Negara Islam, Fakultas Syariah, Universitas Islam Negeri (UIN) Datokarama Palu, 2020)
The existence of community organizations such as Muhammadiyah in Yogyakarta, and Nahdathul Ulama in East Java, Nahdhatul Wathon in West Nusa Tenggara has a very significant role in making changes for the progress of the nation. These roles can be seen especially in the fields of education and community development. Meanwhile for the Sulawesi region, especially Central Sulawesi, many of these roles were taken over by the Al-Khairaat Institution or College which was founded by Sayyid Idrus bin Salim Al-Jufri or who is familiarly called Guru Tua. The role of Al-Khairaat is especially in the field of educational development. As the Al-Khairaat Islamic Education Institute is a national struggle institution that seeks to form people who believe and have faith in Allah SWT, this institution bears the burden of moral responsibility and ideas for the life and development of Islamic education, for the benefit and improvement of the quality of the ummah.